The matching process: Search or mismatch? - Nils Gottfries; Karolina Stadin (Uppsala University, Department of Economics, 2016)
We examine the matching process using monthly panel data for local labour markets in Sweden. We find that an increase in the number of vacancies has a very weak effect on the number of unemployed workers being hired: unemployed workers appear to be unable to compete for many available jobs. Vacancies are filled quickly and there is no (or only weak) evidence that high unemployment makes it easier to fill vacancies; hiring appears to be determined by labour demand while frictions and labour supply play small roles. These results indicate persistent mismatch in the Swedish labour market.
urn:nbn:se:uu:diva-308304
Keywords: J23; J62; J63; J64; 330; structural unemployment; frictional unemployment; matching function; labour demand; labour supply